Pangean Silat: Community Education in Traditional Malay Weddings - Nur Aprianti, Suci; Daryusti, Daryusti (IJORER : International Journal of Recent Educational Research, 2026)
This research aims to examine the formal aspects of the Silat Pangean dance, specifically its presentation style, function, and historical context, within traditional Malay wedding ceremonies in Mak Teduh Village. A qualitative methodology was employed over two months (June–July 2023) to investigate this complex social phenomenon. Subjects included the bride and groom, Silat Pangean teachers, dancers, musicians, and traditional and village leaders from Mak Teduh. Data were collected through observation, in-depth interviews, and document analysis. The analysis utilised data reduction, presentation, and conclusion-drawing techniques, while data veracity was ensured through source and method triangulation. The formal presentation of the Silat Pangean dance consists of four primary elements: (1) Movement, which includes togak ali, ompat steps, conncang, tikam, popat, and simbuh; (2) Floor design, utilising both straight and curved lines; (3) Musical accompaniment, featuring two drums and one tak-tawak; and (4) Costuming, which relies on standard attire without specialised make-up or clothing. This study provides a detailed, localised documentation of the formal choreographic structures and presentation styles of the Silat Pangean dance, specifically within Mak Teduh Village, preserving and analysing a specific cultural asset that has previously lacked comprehensive formal analysis in the context of informal community education.